Mucosal DNA methylome alteration in Crohn’s disease: surgical and non-surgical groups - Ahmad, Saeed; Sands, Mia; Greenberg, Eugene; Tangen, Lyn; Huang, Jiacheng; Irudayaraj, Joseph Maria Kumar (Frontiers in Genetics, 2023)
Crohn's disease (CD) is characterized as a chronic, relapsing, and progressive disorder with a complex etiology involving interactions between host, microbiome, and the external environment. Genome wide association studies (GWAS) suggest several genetic variations in the diseased individuals but that explains only a small proportion of susceptibility to disease conditions. This indicates the possible role of epigenome which links environmental factors to the genetic variation in the disease etiology. The current study is focused on the DNA methylome evolution with disease progression. We performed Reduced Representation Bisulfite Sequencing (RRBS) to analyze differential DNA methylation in the diseased and healthy mucosal tissues of 2 different groups of CD patients: non-surgical and surgical, categorized based on the severity of disease and standard of care needed. Patients in both groups have unique DNA methylation signature compared to the healthy tissue. After removing single nucleotide polymorphisms (SNPs), 1,671 differentially methylated loci were found in the non-surgical and 3,334 in the surgical group of which only 206 were found overlapping in both groups. Furthermore, differential DNA methylation was noted in some of the GWAS associated genes implicated in CD. Also, functional enrichment analysis showed high representation of several key pathways where differential methylations were observed, and these can be implicated in CD pathogenesis. We identified specific DNA methylation patterns in the mucosal DNA of surgical and non-surgical CD patients which indicates evolution of the methylome as the 2 This is a provisional file, not the final typeset article disease progresses from initial to the advance stage. These unique patterns can be used as DNA methylation signatures to identify different stages of the disease.